COMPARATIVE ASSESSMENT OF ANNUAL SPARSELY DISTRIBUTED FORAGE CROPS BY PRODUCTIVITY IN THE CONDITIONS OF THE STEPPE ZONE OF NORTHERN KAZAKHSTAN - Tynykulov, M. K.; Tleppaeva, A. A.; Kurmangaliev, M. K.; Arystanova, Sh. E.; Kosanov, S. U. (ЗКАТУ им. Жангир хана, 2024)
The article presents the results of a comparative assessment of non-traditional annual fodder crops in terms of productivity in the steppe zone of Northern Kazakhstan. The object of research are varieties and hybrids of sorghum-Sudanese hybrid, corn, paisa and African millet. The purpose of the research is to conduct a comparative assessment of forage crops by productivity in the conditions of the steppe zone of Northern Kazakhstan. The relevance of the research topic lies in the selection and introduction of new, more productive and drought-resistant forage crops for the steppe zone of Northern Kazakhstan. The objectives of the research include to study the peculiarities of the cultivation of forage crops in the steppe zone of Northern Kazakhstan; to conduct a comparative assessment of the yield of forage crops; to determine the most promising for cultivation in the steppe zone of Northern Kazakhstan forage crops. The scientific significance of the work lies in obtaining new data on the comparative yield of various forage crops in the conditions of the steppe zone of Northern Kazakhstan. Contribution of the work: the obtained data on the comparative yield of various forage crops in the conditions of the steppe zone of Northern Kazakhstan will improve the efficiency of agricultural production. The practical significance and value of the work lies in the development of recommendations on the selection of the most promising forage crops for cultivation in the steppe zone of Northern Kazakhstan, as well as for the introduction of adaptive technologies into agricultural production. The following research methods are used in the work: B.A. Dospekhov's experimental case methodology, D.D. vegetation accounting method. Brown, N.M. Bakaev's method of determining soil moisture; laboratory analyses; mathematical processing of yield data. According to the results of the research, it was found that the sorghum-Sudank hybrid formed the highest yield: 209.1 c/ha of green mass and 32.6 c/ha of dry matter. Corn and sorghum-sudank hybrid showed a balanced feed content of crude protein and crude fiber. Payza and African millet have a lower, but reasonably high yield than corn and sorghum-a Sudanese hybrid.
Tynykulov , M. K. comparative assessment of annual sparsely distributed forage crops by productivity in the conditions of the steppe zone of northern Kazakhstan / M. K. Tynykulov , A. A. Tleppaeva, M. K. Kurmangaliev, Sh. E. Arystanova, S. U. Kosanov. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-2 (75). Ч. ІІ. - Р. 95-104.
Keywords: sorghum-sudanese hybrid; payza and African millet; yield; green mass; dry matter; научный журнал; зкату